Strategic Formulation for Tour Guide Competency Development: An Integrated AHP–TOWS Approach - Susanto, Eko; Utomo, Sherly Rakasiwi Putri; Chendraningrum, Dinarsiah; Septyandi, Chandra Budi (Journal of Tourism, Hospitality and Travel Management, 2024)
As tourism becomes increasingly experience-driven and sustainability-focused, the role of tour guides has evolved into a strategic touchpoint that shapes visitor perceptions and destination image. This study aims to formulate and prioritize effective strategies for tour guide competency development using an integrated Analytical Hierarchy Process (AHP) and quantitative TOWS matrix approach. A panel of twelve experts representing government, training institutions, and tourism practitioners participated in structured pairwise comparisons and SWOT-based strategy scoring. The AHP results revealed that experiential learning-based training and national certification systems are the most critical and high-impact strategies supported by public-private partnerships and emerging digital tools. Through the TOWS mapping, each strategy was evaluated for its strategic fit within Strengths, Weaknesses, Opportunities, and Threats (SWOT), resulting in a prioritized roadmap for implementation. The study concludes that a tiered, context-sensitive strategy—grounded in institutional collaboration and adaptive learning models—offers a sustainable path to professionalizing the guiding sector. This research provides actionable insights for policymakers, tourism educators, and destination managers seeking to build resilient and skilled human capital in tourism.